A comprehensive view of global potential for hydro-generated electricity. Issue 9 (26th September 2015) - Zhou, Y.; Hejazi, M.; Smith, S.; Edmonds, J.; Li, H.; Clarke, L.; Calvin, K.; Thomson, A.
<x xml:space="preserve">Abstract</x> This study provides the first comprehensive quantification of global hydropower potential including gross, technical, economic, and exploitable estimates.